Implementasi Tahapan P.O.S.T Pada Program Sekolah Ramah Anak Dalam Kegiatan Sosialisasi KBGO Studi Kasus di SMP Negeri 5 Kota Cirebon - Simanjuntak, Stefanie Natalia; Prasetio, Arie (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The development of technology, especially during the COVID-19 pandemic, has changed the patterns of community activities, encouraging a shift to remote activities through the internet and social media. Although it provides convenience, the increasing use of the internet also has negative consequences, especially related to the phenomenon of online gender-based violence (KBGO). This study refers to the implementation of the P.O.S.T. (people, objectives, strategy, and technology) stages in the Friendly School program to socialize the dangers of KBGO in SMP Negeri 5 Kota Cirebon. The method used is a qualitative method with a descriptive case study approach. The results of this study explain the implementation of the P.O.S.T. stages in the social marketing strategy on social media at Friendly School program in SMP Negeri 5 Kota Cirebon, which is effective in socializing the dangers of KBGO. The socialization carried out aims to provide new insights related to the prevention and handling of KBGO and to build a safe environment for individuals who are vulnerable to becoming victims, especially in the context of SMP Negeri 5 Kota Cirebon students.